Compound Astragalus and Salvia miltiorrhiza extracts modulate MAPK-regulated TGF-β/Smad signaling in hepatocellular carcinoma by multi-target mechanism. (1st July 2015) - Boye, Alex; Wu, Chao; Jiang, Yufeng; Wang, Jiyu; Wu, Jiajun; Yang, Xiaochuan; Yang, Yan
Abstract: Ethnopharmacological relevance: Astragalus membranaceus Bunge (Leguminosae) and Salvia miltiorrhiza Bunge (Lamiaceae) are two important Chinese herbs with a long history of extensive ethnobotanical usage in the treatment of liver-related diseases over many centuries. Presently, these two herbs are being used either as a single herbal formulation or a composite formula for the treatment of liver related conditions. In response, recent studies on these two herbs have focused on elucidating their mechanisms of action, particularly with regards to their anti-hepatocarcinogenic effects. Previously, we have reported that Compound Astragalu s and Salvia miltiorrhiza extract (CASE), a synergized composite extract from Astragalus membranaceus and Salvia miltiorrhiza ameliorates liver fibrosis and hepatocellular carcinoma (HCC) by modulating the TGF-β/Smad pathway. Meanwhile, MAPK activation and MAPK-dependent linker phosphorylation of Smad2/3 and their preferential nuclear import are crucial for overall oncogenic role of TGF-β/Smad signaling in HCC. To elucidate further, we studied the effect of CASE on the MAPK pathway and how it affects MAPK-dependent regulation of TGF-β/Smad signaling using both cell and animal models of HCC. Materials and methods: We used immunofluorescence and western blot techniques to monitor effect of CASE on the activation of the MAPKs (pERK, pJNK and pp38) in TGF-β1 -stimulated hepatic stellate cells (HSCs), HepG2 cells and also diethylnitrosamine (DEN)-induced HCC in rats. Also phosphorylation and subcellular distribution of pSmad2/3, Smad4 and Imp7/8 in TGF-β1 -stimulated HSC and HepG2 cells were monitored. The expression of pERK, pJNK, pp38 and PAI-1 gene were monitored by using western blot technique. The effect of CASE on domain-specific phosphorylation of Smad2/3 and their subcellular distribution, and the expression of Smad4 and its subcellular distribution in TGF-β1 -stimulated HSCs and HepG2 cells were evaluated by using immunofluorescence technique. And the expression of Imp7/8 and their subcellular distribution were assessed by both immunofluorescence and western blot techniques, while PAI-1 gene expression was assessed by western blot Results: In vitro, CASE in a concentration-dependent manner increased the expression of pp38 but decreased the expression of pERK and pJNK; however, in vivo, CASE in a dose dependent manner decreased the expression of pERK, pJNK as well as pp38. Also, CASE concentration dependently inhibited pSmad2C/L, pSmad3L, Smad4, Imp7/8 and their nuclear import; it had no effect on pSmad3C in HepG2 cells; significantly decreased PAI-1 gene expression in both in vitro and in vivo . Conclusions: CASE blocked MAPK activation, MAPK-dependent linker phosphorylation of Smad2/3, Smad4 expression, Imp7 expression and their nuclear import leading to significant down-regulation of PAI-1 gene expression; further highlighting the multi-target anti-HCC effect of CASE and its potential drug candidature. Graphical abstract: